Unraveling Cyber Abuse: A Global Perspective - Sanjaya, Yusrizal; Rosnawati, Emy; Indakto, Ratro (Proceedings of The ICECRS, 2023)
This research delves into the pervasive issue of cyber abuse within the realm of cyber law, employing data from Lens.org to unravel critical insights. By searching scholarly works using keywords "Cyberlaw OR Cyber Law AND Abuse" and filtering the results to focus on the legal category, a comprehensive dataset comprising 22,138 journal articles was curated. The study sheds light on the evolution of cyber abuse from 2015 to 2020, indicating a persistent concern despite slight declines in recent years. Psychology emerged as the primary field of study, with 6,971 journals dedicated to the topic, followed closely by Criminology and Sociology. The most active institutions in addressing abuse-related subjects include Deakin University, University of Nebraska, School of Law, and University of Washington. Noteworthy trends were observed in the geographical distribution of research efforts, emphasizing the global impact of cyber abuse. The data also uncovered a prolific scholarly output, with institutions and authors actively contributing to the discourse. This dataset serves as a crucial resource for legal scholars, policymakers, and law enforcement agencies, offering deep insights into the multifaceted challenges of cyber abuse and paving the way for informed legal reforms and social interventions. Highlights : Persistent Concern: Cyber abuse remains a pressing issue despite minor declines, highlighting the need for continuous research and legal interventions. Diverse Research Landscape: Psychology emerges as a dominant field, emphasizing the multidisciplinary nature of cyber abuse studies. Global Collaboration: Active institutions worldwide contribute to the discourse, underlining the global nature of the problem and the necessity for international collaboration. Keywords: Cyber Law, Cyber Abuse, Legal Research, Psychology, Global Impact